The Effect of Using Genially Media on Food Technology Learning Outcomes for Culinary Education Students - Erli Mutiara; Siti Sutanti; Dian Agustina Dalimunthe; Rossy Luckita Sasmita (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
The research employs a quasi-experimental design and was conducted within the Culinary Education Study Program at Universitas Negeri Medan from July to September 2024. The study population includes all Culinary Education students in classes A, B, C, and D, totaling 93 students. A random sampling technique was used to select the sample, resulting in class A with 30 students as the experimental group using Genially media, and class B with 30 students as the control group using PowerPoint. Data were collected through pre-test and post-test learning outcome scores. Data analysis techniques include descriptive statistics, assumption tests (normality and homogeneity tests), and hypothesis testing using a t-test. The research findings indicate that scores in the Genially group fell predominantly in the "very good" category at 53.33%, while the PowerPoint group showed only 3.33% in this category, which was rated as poor. The normality and homogeneity tests confirm that both groups’ data are normally distributed with homogeneous variances. The t-test results reveal a significant positive effect of using Genially media on students’ learning outcomes, with the obtained t-value (t = 11.88) exceeding the critical t-value (t = 2.00, p < 0.05). This suggests that Genially media can positively influence the Food Technology learning outcomes of Culinary Education students. The study concludes by recommending Genially as a widely applicable tool in vocational education, especially in courses requiring visualizations and an understanding of complex concepts.